IMPLEMENTASI DIGITAL LEADERSHIP DALAM PENGEMBANGAN INNOVATION LEARNING PADA PERGURUAN TINGGI SWASTA DI SULAWESI TENGGARA - Abdul Hamid; Risman Iye (JISEF : Journal Of International Sharia Economics And Financial, 2026)
This study aims to investigate the implementation of digital leadership in private higher education institutions in the digital era. The study examines the roles of visionary leadership, digital learning culture, professional excellence, systemic improvement, and digital citizenship in influencing the performance of private universities (PTS) in Southeast Sulawesi. An online questionnaire survey was adopted, and a non-probability sampling method using purposive sampling was applied. A total of 81 usable responses were collected from leaders of private higher education institutions in Southeast Sulawesi and analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.3. The results show that digital learning culture, professional excellence, and digital citizenship have a positive effect on institutional performance. However, visionary leadership and systemic improvement do not show a statistically significant positive relationship with performance.These findings provide insights for researchers and future leaders in private higher education institutions regarding the important roles of digital learning culture, professional excellence, and digital citizenship in contemporary institutions. The novelty of this study contributes to the body of knowledge on digital leadership and institutional performance within the context of private higher education institutions in emerging markets.